The Modernization of China: Armenia-China Relations - Araks Pashayan (Banber Arevelagitut'yan Instituti)
On 12 November 2024, the Institute of Oriental Studies of NAS RA, with the support of the Bryusov State University (BSU), organized an international conference entitled “The Modernization of China: Armenia-China Relations.” The conference addressed China's modernization, Beijing's vision for current international relations, global security issues, universal human development, and welfare issues. Moreover, the conference aimed to examine the dynamics of Armenia-China relations, their weak and strong sides, and current tendencies. Researchers from the Institute of Russian, East European, and Central Asian Studies of the Chinese Academy of Social Sciences, a major partner of the Institute of Oriental Studies (IOS), Renmin University of China, and Beijing University of Aviation and Astronautics, participated in the conference. From the Armenian side, researchers from the Institute of Oriental Studies of the NAS RA, BSU, the Armenian State University of Economics, and representatives of institutions cooperating with China participated in the conference.